2016
DOI: 10.1515/aiht-2016-67-2708
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin ameliorates pathological changes in liver and kidney of diabetic mice: a preliminary study / Naringenin reducira histopatološke promjene u jetri i bubregu miševa s dijabetesom

Abstract: The effect of naringenin, a flavonoid found in grapefruit, orange, and tomato, on lipid peroxidation and histopathological changes in the liver and kidneys of alloxan-induced diabetic mice were investigated. Two days after alloxan injection (75 mg kg -1 , i.v.), naringenin ethanolic solution (0.5 % v/v) was given to mice intraperitoneally (50 mg kg -1 per day) for seven days. Naringenin's impact on lipid peroxidation was measured by the 2-thiobarbituric acid test and histopathological changes were examined und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…As a type of flavonoid, Nar is the predominant flavanone in grapefruit and is found to have strong anti-inflammatory, antioxidant, and organ-protective activities. A previous study has indicated that Nar alleviates the histopathological changes in the liver and kidney caused by alloxan-induced diabetes in mice [ 20 ]. Nar can downregulate TNF-a, IL-1 β , IL-6, IL-10, and other inflammatory cytokines in macrophages infected with live Chlamydia trachomatis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a type of flavonoid, Nar is the predominant flavanone in grapefruit and is found to have strong anti-inflammatory, antioxidant, and organ-protective activities. A previous study has indicated that Nar alleviates the histopathological changes in the liver and kidney caused by alloxan-induced diabetes in mice [ 20 ]. Nar can downregulate TNF-a, IL-1 β , IL-6, IL-10, and other inflammatory cytokines in macrophages infected with live Chlamydia trachomatis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that, in diabetic rats, naringenin reduced diabetic markers through PPARγ and glucose transporter Type 4 (GLUT4) and increased their gene and protein expression levels in pancreas [36]. In the liver, naringenin increased glycogen content, decreased activities of glycogen phosphorylase and glucose-6-phosphatase [37] and ameliorated diabetes induced hepatotoxicity [38]. In the extracts from M. charantia, compounds like rutin and daidzein and naringenin are the most common, but epicatechin (-) is the one with the highest concentration (143.34 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that, in diabetic rats, the flavonoid reduced diabetic markers through PPARγ and glucose transporter type 4 (GLUT4) and increased their gene and protein expression levels in pancreas[ 210 ]. In the liver, naringenin increased glycogen content, decrease activities of glycogen phosphorylase and glucose-6- phosphatase[ 211 ] and ameliorated diabetes-induced hepatotoxicity[ 212 , 213 ]. For more information see Nyane et al[ 214 ].…”
Section: Antidiabetic Effect Of Naringeninmentioning
confidence: 99%